Mechanical Characterization of APA Microcapsules by Parallel-Plate Compression - Bando, Kiyoshi; Yamaguchi, Yohei (Journal of Membrane and Separation Technology, 2017)
We produced microcapsules of alginate-poly(L)lysine-alginate (APA)with diameters on the order of 10 µm. To characterize their mechanical properties, we conducted an experiment on the parallel-plate compression of a microcapsule and modeled its deformation. In the modeling task, the microcapsule was assumed to be a spherical liquid-filled elastic membrane with negligible bending stiffness and permeability. The membrane thickness was estimated by applying Reissner's linear elastic theory to the experimental force-displacement relationship during loading in the small displacement region. The initial stretch of the membrane was taken into account; it was mainly caused by the osmotic pressure difference across the membrane. The initial stretch of the microcapsule was determined by fitting the calculated and experimental force-displacement relationships during loading at small to medium displacements. At large displacements, the calculated force was smaller than the experimentally measured force because of fluid permeation across the APA membrane. The calculated and experimentally imaged shapes of the deformed microcapsule were compared. The effects of varying the membrane thickness on the force-displacement and transmural pressure-displacement curves were shown, and the limitations of applying the present deformation model were examined.